(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
This study explores the use of umbilical cord blood for DNA profiling in paternity disputes, offering a practical alternative to traditional fetal or neonatal blood sampling with higher yield and no maternal contamination.